2480 MA MAFIC MAGMATISM IN THE NORTHERN BLACK HILLS, SOUTH DAKOTA: A NEW LINK CONNECTING THE WYOMING AND SUPERIOR CRATONS - Dahl P.S.; Hamilton M.A.; Wooden J.L.; Foland K.A.; Frei R.; McCombs J.A.; Holm D.K. (My University, 2006)
The Laramide Black Hills uplift of southwest South Dakota exposes a Precambrian crystalline core of ~2560-2600 Ma basement granitoids nonconformably overlain by two Paleoproterozoic intracratonic rift successions. In the northern Black Hills, a 1 km thick, layered sill (the Blue Draw metagabbro) that intrudes the older rift succession provides a key constraint on the timing of mafic magmatism and of older rift-basin sedimentation. Ion microprobe spot analyses of megacrysts of magmatic titanite from a horizon of dioritic pegmatite in the uppermost sill portion yield a 207Pb/206Pb upper-intercept age of 2480 ± 6 Ma (all age errors ±2σ), comparable to two-point 207Pb/206Pb errorchron ages obtained by Pb stepwise leaching of the same titanites. Nearly concordant domains in coexisting magmatic zircon yield apparent spot ages ranging from 2458 ± 16 to 2284 ± 20 Ma (i.e., differentially reset along U-Pb concordia), and hornblende from an associated metadiorite yields a partially reset date with oldest apparent-age increments ranging between 2076 ± 16 and 2010 ± 8 Ma. We interpret these data as indicating that an episode of gabbroic magmatism occurred at 2480 Ma, in response to earlier rifting of the eastern edge of the Wyoming craton. Layered mafic intrusions of similar thickness and identical age occur along a rifted belt in the southern Superior craton (Sudbury region, Ontario). Moreover, these mafic intrusions are spatially aligned using previous supercontinent restorations of the Wyoming and Superior cratons (Kenorland-Superia configurations). This new "piercing point" augments one previously inferred by spatial-temporal correlation of the Paleoproterozoic Huronian (southern Ontario) and Snowy Pass (southeastern Wyoming) supergroups. We propose that layered mafic intrusions extending from Nemo, South Dakota, to Sudbury, Ontario, delineate an axial rift zone along which Wyoming began to separate from Superior during initial fragmentation of the Neoarchean supercontinent at ≥2480 Ma. © 2006 NRC Canada.
Keywords: Paleoproterozoic; Neoarchean; Eoarchean; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская; Precambrian::Archean::Neoarchean; Докембрий::Архей::Неоархейская; Precambrian::Archean::Eoarchean; Докембрий::Архей::Эоархейская